Performance and Emission Analysis of Rubber Seed Methyl Ester and Antioxidant in a Multicylinder Diesel Engine - Adam, I.K. (American Chemical Society, 2017)
In this study, the potential of using a nonedible biodiesel source (rubber seed oil) was explored. Rubber seed oil (RSO) is a promising nonedible source for producing a sustainable biodiesel in Malaysia. However, due to the lower oxidation stability of the produced biodiesel, which is the result of its higher unsaturation content (78.73), an oxidation inhibitor is required. This paper examines the effect of antioxidants addition to rubber seed biodiesel (RB) on the combustion, engine performance, and emissions. Four antioxidants, namely, N,N′-diphenyl-1,4-phenylenediamine (DPPD), 2-tert-butylbenzene-1,4-diol (TBHQ), N-phenyl-1,4-phenylenediamine (NPPD), and 2(3)-tert-butyl-4-methoxyphenol (BHA), were added at concentrations of 1000 and 2000 ppm to 20 RB (RB20). The results showed that TBHQ had the greatest ability to increase the stability of RB20 followed by BHA, DPPD, and NPPD, respectively, without a significant effect on physical properties. The experiments were conducted in a 55 kW multicylinder diesel engine at full load conditions. The results showed that RB20 produced a lower brake power (BP) of 3.07, higher brake specific fuel consumption (BSFC) of 3.68, and higher maximum in-cylinder pressure of 6.7 compared to neat diesel. Antioxidants addition reduced the NO, heat release rate (HRR), and maximum in cylinder pressure by an average of 0.85- 4.12, 5.78-14.74, and 1.77-3.97, respectively, compared to RB20. All antioxidant fuels showed a similar start of combustion (-12°CA BTDC), but for diesel and RB20 the values were -10 and -13°CA BTDC, respectively. However, carbon monoxide (CO) and hydrocarbon (HC) emissions increased by 10.17- 15.25 and 13.35-19.68, respectively, compared to RB20. It can be concluded that the RB20 blend treated with antioxidants can be used in diesel engines without any further modifications. © 2017 American Chemical Society.